Mixed methods Participatory Action Research to inform service design based on the Capabilities Approach, in the North of England. (22nd September 2021) - Shearn, Katie; Brook, Anna; Humphreys, Helen; Wardle, Carrie
Abstract: Proponents of the Capabilities Approach advocate that young people should be able to live lives they have reason to value, supported by public services. Mixed‐methods Participatory Action Research involving 47 young people aged 13–16, five practitioners, and one commissioner was carried out to develop a local Capabilities Framework. The framework had five themes: 'people and relationships', 'places, spaces and time for me', 'learning and skills', 'freedoms, rights and responsibilities' and 'health and wellbeing'. Recommendations for service design include cross‐sector working to support the promotion of social opportunities and services, and interventions focused on the strengths of each young person.